Effect Of Intaking High-Fat Diet On White Rat’s (Rattus norvegicus)Blood Lipid Profil - Made Subawa Harsa (Universitas Wijaya Kusuma Surabaya, 2014)
Obesity and metabolic syndrom are characterized by dislipidemia. One of methods that is performed to increase body fat contents is by intaking of high-fat diet. The purpose of this study was to demonstrate the effect of a dietary intake of high-fat on the lipid profile (total cholesterol, HDL, LDL, and triacylglycerol) in white rat (Rattus norvegicus). This research was tested on 30 white rats that were divided into 2 randomized groups, and were treated for 4 weeks. Group 1 (K1) : was treated with standard diet, (K2) : with standard and high-fat diet. The results showed that intaking high-fat diet increases the total cholesterol content, triacylglycerol, LDL cholesterol, and decreases HDL cholesterol content.